Evidence of Inflammatory Network Disruption in Chronic Venous Disease: An Analysis of Circulating Cytokines and Chemokines - Oscar Fraile-Martinez; Cielo García-Montero; Ana María Gomez-Lahoz; Felipe Sainz; Julia Bujan; Silvestra Barrena-Blázquez; Laura López-González; Raul Díaz-Pedrero; Melchor Álvarez-Mon; Natalio García-Honduvilla; Miguel A. Saez; Jorge Monserrat; et al. (Biomedicines)
Background: Chronic venous disease (CVD) comprises a set of vascular disorders that affect the venous system with important local and systemic repercussions. A growing body of evidence displays the relationship between suffering from CVD and a marked deregulation of the immune inflammatory system. In this sense, the previous literature has reported some significant changes in the level of various circulating inflammatory parameters in these patients. However, more research is required to detail and deepen this complex relationship. Methods: In this work, we studied, using a multiplex technique, the levels of circulating cytokines and chemokines detectable in the serum of 40 patients with CVD and compared it with 38 healthy controls (HCs). In parallel, we performed Spearman’s correlation analysis to explore potential inflammatory networks in CVD. Results: In this study, we measured circulating cytokines and chemokines in CVD patients using a multiplex assay. Results showed increased levels of several pro-inflammatory mediators (IL-1β, IL-2, IL-5, IL-6, IL-7, IL-8, IL-12, IL-17A, IL-23, TNF-α, IFN-γ, fractalkine, ITAC, and GM-CSF) and a decrease in IL-13, with no significant changes in IL-4, IL-10, IL-21, MIP-1α, MIP-1β, or MIP-3α. The Spearman correlation analysis revealed strong, positive correlations among several inflammatory mediators in HC, particularly between TNF-alpha, IL-1β, IL-17A, and IL-23, forming a highly interconnected cytokine network. In contrast, CVD patients showed fewer, weaker, and distinct correlations, with new associations such as IFN-γ with IL-1β and IL-23, suggesting a disrupted inflammatory profile. Conclusions: The distinct inflammatory profile in CVD patients, characterized by altered cytokine and chemokine levels and a less coordinated cytokine network, underscores the reconfiguration of inflammatory pathways in this condition. These findings highlight potential therapeutic targets aimed at restoring immune balance and mitigating chronic inflammation in CVD.